Physical Disability Affects Women’s but Not Men’s Perception of Opposite-Sex Attractiveness - Pazhoohi, Farid; Capozzi, Francesca; Kingstone, Alan (Frontiers in Psychology, 2021)
Physical appearance influences our perceptions, judgements, and decision making about others. While the current literature with regard to the perceptions and judgements of nondisabled people’s attractiveness is robust, the research investigating the perceived physical attractiveness and judgements of physically disabled individuals are scarce. Therefore, in the current study we investigated whether people with physical disabilities are perceived by the opposite sex as more or less attractive relative to nondisabled individuals. Our results, based on over 675 participants, showed a positive effect for women’s attractiveness ratings of men with physical disabilities, but not men’s attractiveness ratings of physically disabled women. Moreover, social desirability bias was positively associated with attractiveness ratings of physically disabled individuals, meaning those with higher tendency to be viewed favorably by others rated physically disabled individuals more attractive. Finally, our results revealed that attractiveness ratings of individuals with physical disabilities are positively associated with extroversion and empathy in both men and women, and positively with agreeableness and negatively with neuroticism in women. In conclusion, our study showed women rate men with physical disabilities as higher on attractiveness than nondisabled men, which is also influenced by their social desirability bias.